A bird's-eye view to the monthly pattern of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in the world, 2012 until 2016 - Kazhal Mobaraki; Jamal Ahmadzadeh (Global Journal of Rare Diseases - Peertechz Publications, 2019)
This issue is better appreciated in the graph for 2015 in which two peaks were evident, the fi rst peak is related to cold months (February, March, and April) and the second was occurred in warmer months of the year (May, June, July, and August), (Figure 1). This fi nding probably refl ects the effect of the accumulation of indoor air during the cold months, which increases the rate of spread of the disease. Also, the peak of infection seen during the warmer months coincides with the largest mass gathering of Muslims around the world in Saudi Arabia (where it is reported that >80% of MERS-CoV cases occur worldwide) to perform the Hajj and Umrah ceremonies. All this is evidence that the virus seems to pass easily from person to person, particularly in close contact. The trends of incidence of MERS-CoV in the different months within the study period also indicate a downward trend of reported MERS-CoV cases from 2015 to 2016 in fi gure 1 which was due to the effective involvement of the national health authorities.